2022
DOI: 10.1097/j.pain.0000000000002632
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of studies in which burrowing behaviour was assessed in rodent models of disease-associated persistent pain

Abstract: Burrowing behaviour is used to assess pain-associated behaviour in laboratory rodents. To gain insight into how models of diseaseassociated persistent pain and analgesics affect burrowing behaviour, we performed a systematic review and meta-analysis of studies that assessed burrowing behaviour. A systematic search in March 2020 and update in September 2020 was conducted in 4 databases. Study design characteristics and experimental data were extracted, followed by a random-effects meta-analysis. We explored the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 67 publications
2
5
0
Order By: Relevance
“…Because of these limitations of reflexive behaviors to assess pain and analgesia following interventions intended to mimic chronic pain, a variety of other methods have been explored, which reflect ethologically relevant behaviors that are impacted by inferred pain. These include burrowing, 12,21,22 thigmotaxis, [23][24][25][26][27][28] facial grimacing, 29 weight bearing, 30 gait analysis, 31 and conditioned place preference or avoidance. 32 However, these are commonly used by a small December 2022 • Volume 135 • Number 6 www.anesthesia-analgesia.org 1133 minority of laboratories and are rarely declared as primary outcomes over reflexive measures.…”
Section: Outcome Measures To Infer Painmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of these limitations of reflexive behaviors to assess pain and analgesia following interventions intended to mimic chronic pain, a variety of other methods have been explored, which reflect ethologically relevant behaviors that are impacted by inferred pain. These include burrowing, 12,21,22 thigmotaxis, [23][24][25][26][27][28] facial grimacing, 29 weight bearing, 30 gait analysis, 31 and conditioned place preference or avoidance. 32 However, these are commonly used by a small December 2022 • Volume 135 • Number 6 www.anesthesia-analgesia.org 1133 minority of laboratories and are rarely declared as primary outcomes over reflexive measures.…”
Section: Outcome Measures To Infer Painmentioning
confidence: 99%
“…Systematic review and meta-analysis of preclinical studies can be a rich unbiased source of the data required to inform sample size calculations. [10][11][12][13] The use of appropriate sample sizes mitigates against the impact of underpowered studies, which have greater risks of generating false-positive results and exaggerating effect sizes. While there is an ethical imperative to use the minimal number of animals necessary in an experiment, it is also true that an underpowered experiment in which little faith can be placed in the results is equally unethical.…”
Section: Internal Validitymentioning
confidence: 99%
See 1 more Smart Citation
“…We were also unable to ascertain differences in thigmotactic outcomes between strains because of the predominant use of Sprague-Dawley and Wistar rats and C57BL/6 mice. This issue of homogeneity in the rodent strain used for preclinical pain research has been observed in other systematic reviews [40][41][42]. Studies have shown that modification of behavioural outcomes caused by disease models associated with persistent pain is strain dependent [43][44][45].…”
Section: Plos Onementioning
confidence: 87%
“…We could not discern the influence of sex on thigmotactic outcomes because male animals were predominantly used. In other preclinical systematic reviews of pain, sex accounted for a significant proportion of the heterogeneity [40][41][42]48]. Women are clinically prone to be affected by chronic pain and tend to experience greater pain intensity than men [8].…”
Section: Plos Onementioning
confidence: 99%